Energy and emission analysis of flash ironmaking-powder generation coupling processes with various fuels. (25th November 2022) - Yang, Yiru; Shen, Zhongjie; Wen, Xiaochun; Liu, Haifeng
Highlights: The full-cycle flash ironmaking-power generation process was firstly investigated. The sensitivity analysis provides optimum conditions during the different stages. Direct use of biomass is not recommended with highest fuel ratio Rf = 4.3. Hydrogen was proved the most effective with the high exergy efficiency (48.6 %). The chemical exergy in hot metal (31–34 MJ) helps improving the system efficiency. Abstract: The flash ironmaking-power generation coupling (FIPG) process combines the latest entrained-flow bed ironmaking technology and efficient cycle power generation. Different fuels (hydrogen, methane, coal, and biomass) are adopted to produce the reducing gas components. In this study, the process simulation was established based on the Gibbs free energy minimize principle, and FIPG included the flash ironmaking coupling (FIC), settler heating (SH), and combined cycle power (CCP) processes. The sensitivity analysis determined the optimum conditions (fuel ratio RF, oxygen ratio RO, and replenished oxygen ratio R OF ), and we compared mass, energy, and exergy flows in different cases. In FIC, the optimized conditions determined using the crossing points of curves temperature T = 1350 °C and reduction degree X = 0.7 are (H2 : RF = 0.16, RO = 2.11), (CH4 : RF = 0.43, RO = 1.58) and (Coal: RF = 0.59, RO = 0.88). Due to the low heating value of biomass, its optimized RF is higher than others, even with a declined requirement ( X = 0.6) (Biomass: RF = 4.3, RO = 0.39). In SH, except that the SH-biomass requires more replenished fuel, the other three cases slightly differ due to the close first stage particle outputs. A suitable replenished oxygen/coal ratio ( ROR = 0.74) ensures the hot metal's high carburization rate and temperature with fewer fuel amounts. From the energy balance perspective, the fuels account for most heat expenditure, while the electricity produced by CCP accounts for most of the energy benefit. Meanwhile, chemical energy from iron is the third largest expenditure item, with a share ranging from 10.91 % to 21.71 %. Exergy analysis provided a detailed flow chart between processes, showing the highest exergy efficiency (48.6 %) in FIPG-H2 and the lowest (43.0 %) in FIPG-biomass. Although the ore reduction consumes CO to generate the oxidation product CO2, the most significant CO2 generation occurred in the CCP stage. The total CO2 emissions per energy consumption unit are 71.55 Nm 3 /MW, 107.56 Nm 3 /MW, 138.49 Nm 3 /MW, and 148.63 Nm 3 /MW in FIPG-H2, FIPG-CH4, FIPG-coal, and FIPG-biomass.